Los medios educativos en la enseñanza aprendizaje en Educación Inicial - Coronel Lucero, Nélida Karinna (2006)
In general it is considered as educational means those resources that facilitate the process of teaching and learning within a systematic comprehensive educational context, stimulating the function of the senses to more easily access information, to the acquisition of skills and abilities, and the formation of attitudes and values. Educational media for their role in the academic process can be differentiated from other elements or instructional objects that are sometimes confused with the term "medium", ie under the media category of teaching does not fit or forms or organizational modes teaching (such as demonstrations, exhibitions, group work, excursions, etc.) because they do not meet the attribute of "technological resources"; neither can include tools and instruments work and school furniture as neither scissors, markers, paper, or indeed desks, tables or chairs, meet the attribute "symbolize" or transmit messages. The latter are real objects such as animals or plants, but no teaching aids in the sense defined. It has now been inserted strongly in the educational field, so the computer assisted instruction becomes increasingly attractive. This is demonstrated by the rising number of students and teachers who use it. It is scientifically proven that the use of educational media and materials in the learning process are incomparable educational value, since concretized, facilitate and save time and effort in discovering the contents or our reality. The preponderance of the functions of the teaching profession, according as used in the teaching and learning can refer to: provide information, guiding learning, exercise skills, train, evaluate, provide simulations, provide environments for expression and create, innovate, motivate, structuring reality, set cognitive relationship, facilitate educational action form. Without pretending to confuse the classification of materials which is subject to their origin, will be classified from different points of view, for example, there are materials for students, teacher materials, printed materials, audiovisual materials, three-dimensional materials, autoeducativos materials, materials inter-learning, etc. It is necessary that associated with the knowledge of the variety of means that facilitate the teaching and learning process. there teaching skills to select properly, that the criteria that takes into account: that provide safety, that are durable and resilient, having an attractive presentation for children, who have the appropriate size, to allow easy handling, to suit the level of development of students, should encourage the development of curricular competencies that have cultural relevance, they must be multivalent allowing various uses, properly combining price and quality. In addition to criteria, some principles which use to fuse together should be observed: globalization, objectification or intuition, systematization of work. Finally the teacher training necessarily involves aspects to develop skills not to be mere consumers of media produced by others, but as critical users of the media, ie able to select and analyze the means and materials, before, during and after enter them in planning and education, according to other elements that make up the teaching-learning process. Moreover, this critical user should be able to modify, redesign or rework materials and resources selected to suit each situation, in fact flexibility and plasticity of new media and resources compared to traditional more closed and rigid media, widely facilitate this task. Setting them flexible material in their adaptation to different teaching and learning processes and at different times of these processes. This need for adaptation to the materials of learning, leads us to pay increasing attention to the selection and evaluation of existing means, to reflect on its relevance to the objectives planned way we pursue, the characteristics of students. The task of selecting media by teachers acquire greater importance every day for a number of reasons: the importance of mediated learning is acquiring in the teaching-learning current, diversity of means and resources that we, the assume that the insertion of the media in the curriculum necessarily involves reflection and analysis in your selection if you do not want to make a thoughtless use of them, the meaning they acquire in the process of teaching and learning to build confidence content and the teaching and learning environments, the role of mediators that play in the curriculum, and latent, hidden and missing values ​​transmitted by them that will become the attitudes of students even more than the content presented formally justify them